IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NO. 38 TAHUN 2018 DALAM PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TAHUN ANGGARAN 2019 (STUDI KASUS DI BADAN PENDAPATAN, PENGELOLAAN KEUANGAN, DAN ASET DAERAH/BPPKAD KABUPATEN PONOROGO TAHUN 2020) - Kurniawan, Alif (Master of Public Administration, Universitas Slamet Riyadi, 2020)
Talking about regional financial management policies cannot be separated fromthe policy of decentralization and regional autonomy, whereas in reality there arestill many problems found in the process of preparing the Regional GovernmentBudget in Ponorogo District each year.This research aims to describe andanalyze how the implementation of Minister of Home Affairs Regulation No. 38 of2018 in the preparation of the Regional Budget of the 2019 Budget Year alongwith what are the obstacles and supporters of its implementation. This type ofresearch in research uses qualitative research using theories from Mazmanianand Sebastiar as a basis for thinking in reviewing policy implementation that isinfluenced by 3 main variables namely the characteristics of the problem, thecharacteristics of the policy and the characteristics outside the policy. The methodof data collection is done by observation, interviews, and documentation. Theresults showed that in the implementation of the Minister of Home AffairsRegulation No. 38 of 2018, it is known that the inhibiting factors are politicalfactors, factors of the central government, factors of limited funds / funding, aswell as Programmer